Respiratory Deleted in Malignant Brain Tumours 1 (DMBT1) levels increase during lung maturation and infection - Müller, Hanna; End, Caroline; Weiß, Christel; Renner, Marcus; Bhandiwad, A; Helmke, Burkhard Maria; Gaßler, Nikolaus; Hafner, Mathias; Poustka, Annemarie; Mollenhauer, Jan; Pöschl, Johannes (Clinical & experimental immunology, 2008)
Deleted in Malignant Brain Tumours 1 (DMBT1) is a secreted scavenger receptor cysteine-rich protein that binds and aggregates various bacteria and viruses in vitro. Studies in adults have shown that DMBT1 is expressed mainly by mucosal epithelia and glands, in particular within the respiratory tract, and plays a role in innate immune defence. We hypothesized that respiratory DMBT1 levels may be influenced by various developmental and clinical factors such as maturity, age and bacterial infection. DMBT1 levels were studied in 205 tracheal aspirate samples of 82 ventilated preterm and full-term infants by enzyme-linked immunosorbent assay. Possible effects of various clinical parameters were tested by multiple regression analysis. DMBT1 levels increased significantly with lung maturity (P < 0·0001 for both gestational and postnatal age) and in small-for-gestational-age infants (P = 0·0179). An increase of respiratory DMBT1 levels was detected in neonatal infections (P < 0·0001). These results were supported by Western blotting. Immunohistochemical analyses of archived newborn lung sections (n = 17) demonstrated high concentrations of DMBT1 in lungs of neonates with bacterial infections. Our data show that preterm infants are able to up-regulate DMBT1 in infection as an unspecific immune reaction.
Gesehen am 12.09.2023